THE DIFFERENCE OF STUDENTS’ MATHEMATICS LEARNING OUTCOMES TAUGHT BY THINK-PAIR-SHARE AND NUMBERED HEADS TOGETHER MODELS - Hasugian, Krisna Junifer; Napitupulu, Elvis (Universitas Batanghari Jambi, 2024)
The research aims to examine the variance in students' mathematics when instructed use the Think-Pair-Share and Numbered Heads Together models. The study's population comprises all eighth-grade students at SMP Parulian 1 Medan. Two classes were selected from this population for experimental research, each receiving different treatments: Class VIII-3 as Experimental Group II, taught using the Numbered Heads Together (NHT) model, and Class VIII-2 as the sample group, Experimental Group I, instructed using the Think-Pair-Share (TPS) model. Based on the research findings and discussions outlined in the previous chapter, it can be concluded that: The average score of Experimental Group I surpasses that of Experimental Group II, with the posttest average of Experimental Group I amounting to 81.41 while Experimental Group II scored 75.87. Hypothesis testing is thitung = 2.383 > ttabel =1.99962, thus accepting Ha and rejecting H0. Hence, it can be concluded that students' mathematics learning outcomes using the Think-Pair-Share model are higher than using the Numbered Heads Together model.